BOOK REVIEW OF EAT, PRAY, LOVE BY ELIZABETH GILBERT - Syafrul, Aster Sisi (LANTERN (Journal on English Language, Culture and Literature), 2015)
This book review is concerned with Elizabeth Gilbert’s Eat, Pray, Love. Gilbert’s novel is full of real life experience that was undergone by Gilbert herself. Gilbert’s story in this novel triggered the writer’s curiosity to obtain a deep understanding of how the main character deals with how she survives from her anxiety about life.Eat, Pray, Love, which the writer reviews in this final project, is the first edition of Eat, Pray, Love; it was published in 2006 by Penguin Books. The novel has 352 pages and 108 chapters, and it is basically divided into three main parts. Each part explains the story of Gilbert in each country that she visited: Italy, India, and Indonesia respectively.